1990
DOI: 10.1007/bf00229324
|View full text |Cite
|
Sign up to set email alerts
|

GABA, glycine, aspartate, glutamate and taurine in the vestibular nuclei: an immunocytochemical investigation in the cat

Abstract: The distributions of five amino acids with well-established neuroexcitatory or neuroinhibitory properties were investigated in the feline vestibular complex. Consecutive semithin sections of plastic-embedded tissue were incubated with antisera raised against protein-glutaraldehyde conjugates of GABA, glycine, aspartate, glutamate and taurine. This approach allowed us to study the relative densities of the different immunoreactivities at the level of individual cell profiles. The results indicate that in the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 43 publications
7
86
0
Order By: Relevance
“…Immunocytochemical studies have reported glycine-and/or GABAimmunoreactive cell bodies in the LVN (Walberg et al, 1990). These results are consistent with electrophysiological studies showing that inhibitory postsynaptic potentials (IPSPs) in neck motoneurons caused by stimulation of the vestibular nerve are blocked by strychnine (Felpel, 1972).…”
Section: Classification Of Axon Terminalssupporting
confidence: 87%
See 1 more Smart Citation
“…Immunocytochemical studies have reported glycine-and/or GABAimmunoreactive cell bodies in the LVN (Walberg et al, 1990). These results are consistent with electrophysiological studies showing that inhibitory postsynaptic potentials (IPSPs) in neck motoneurons caused by stimulation of the vestibular nerve are blocked by strychnine (Felpel, 1972).…”
Section: Classification Of Axon Terminalssupporting
confidence: 87%
“…Many neurons in the LVN are immunoreactive for antibodies directed against glutamate and some vestibulospinal neurons are retrogradely labelled by tritiated choline (Jones et al, 1986;Walberg et al, 1990). Thus, both glutamate and acetylcholine are possible candidates for excitatory neurotransmission between LVN neurons and spinal neurons.…”
Section: Classification Of Axon Terminalsmentioning
confidence: 97%
“…Synaptic endings in the oculomotor nucleus incorporate L3H]-GABA (Lanoir et al, 1982;Soghomonian et al, 1989), and a high density of GABA-immunoreactive synaptic endings has been observed in the oculomotor and trochlear nuclei (Soghomonian et al, 1989;Spencer et al, 1989Spencer et al, , 1992Spencer and Baker, 1992). Lesions of the superior vestibular nucleus and MLF, furthermore, reduce levels of GABA synthesis in the trochlear nucleus (Roffler-Tarlov and Tarlov, 1975), even though immunohistochemical studies localizing GABA or its synthesizing enzyme, glutamate decarboxylase (GAD), have identified immunoreactive neurons predominantly in the medial, inferior, and, to a lesser extent, superior vestibular nuclei (Nomura et al, 1984;Kumoi et al, 1987;Carpenter et al, 1990;Walberg et al, 1990;Spencer and Baker, 1992). Differential roles of GABA acting on GABAA and GABAn receptors also have been Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Vestibuloocular neurons that project to the oculomotor and trochlear nuclei, however, are immunoreactive to glutamate and/or aspartate (Kevetter and Hoffman, 1991;Carpenter et al, 1992 ). Although glutamate-and aspartate-immunoreactive neurons, in at least some instances, are considered to be distinct populations in other regions of the nervous system (Clements et al, 1987;Hepler et al, 1988), it is possible that individual vestibular neurons may colocalize glutamate and aspartate in addition to GABA andlor glycine (Yingcharoen et al, 1989;Walberg et al, 1990). The colocalization of glutamate and aspartate in neurons (Hepler et al, 1988) and synaptic endings (Tracey et al, 1991;Phend et al, 1992;see, however, Maxwell et al, 1990;Merighi et al, 1991) also has been observed in other regions of the nervous system.…”
Section: Discussionmentioning
confidence: 97%
“…When antisera to glutamate are applied to spinal cord sections, immunoreactive cell bodies are seen in the superficial dorsal horn (Weinberg et al, 1987;Miller et al, 1988) and it was concluded in these studies that the immunoreactive cells were glutamatergic neurons. However, there is much evidence that the presence of glutamate-like immunoreactivity (glutamate-LI) in cell bodies is not a reliable marker for neurons that use glutamate as a transmitter, since the cell bodies of neurons that are thought not to use glutamate (including motor neurons and presumed GABAergic and glycinergic neurons) may possess glutamate-11 (Ottersen and Storm-Mathisen, 1984;Yingcharoen et al, 1989;Walberg et al, 1990). It is thought that, unlike the situation with glycine and GABA, the "metabolic pool" of glutamate is sufficiently large that it can be detected in the cell bodies of many neurons (Fonnum, 1984;Yingcharoen et al, 1989).…”
mentioning
confidence: 99%